Circadian Rhythm Disruption Modulates Plasma Melatonin, Aortic Senescence, and Blood Pressure Homeostasis in Rats - Syarifin, Andi Noor Kholidha; Prijanti, Ani Retno; Arozal, Wawaimuli; Jusman, Sri Widia Azraki (Trends in Sciences, 2026)
Exposure to light at night disrupts circadian homeostasis and suppresses endogenous melatonin production. Melatonin is crucial for blood pressure regulation and exhibits potent antioxidant properties. Sustained oxidative stress in the aorta contributes to endothelial dysfunction and premature aging. This study investigated the effect of nighttime light exposure on plasma melatonin levels, blood pressure, and molecular markers of vascular stress and senescence in rats. Sprague–Dawley rats were assigned to five groups: Control, Dim light (DL), DL with melatonin (DL + Mel), continuous light exposure (CLE), and CLE plus Melatonin (CLE + Mel). Melatonin (10 mg/kg) was administered orally. ELISA quantified plasma melatonin concentrations, and aortic tissue was analyzed to measure glutathione (GSH) content, intercellular adhesion molecule-1 (ICAM-1), interleukin-6 (IL-6), senescence-associated β-galactosidase (SA-β-Gal) activity, and melatonin receptor type 1 (MT1) gene expression. Nighttime light exposure was associated with a marked reduction in circulating melatonin and an elevation in blood pressure. Melatonin supplementation partially restored melatonin levels and attenuated both systolic and diastolic hypertension. In the aorta, DL and CLE exhibited increased ICAM-1 and IL-6 expression, enhanced SA-β-Gal activity, upregulated MT1 expression, and depleted GSH levels. These molecular alterations were mitigated by melatonin treatment. Collectively, these findings demonstrate that nighttime light exposure induces circadian disruption that drives hypertension, endothelial dysfunction, and premature vascular senescence, whereas melatonin supplementation confers significant protective effects. HIGHLIGHTS Sprague-Dawley Rats were subjected to dim and continuous light at night, and treated with melatonin compared to the untreated group. Exposure to light at night reduced melatonin levels and increased blood pressure in rats. Oxidative stress, inflammation, and senescence markers increased in the aorta. Melatonin treatment restored melatonin levels and lowered blood pressure. Melatonin reduced ICAM-1, IL-6, SA β-Gal activity, and preserved GSH content. GRAPHICAL ABSTRACT